CASE STUDY COMMUNITY MIDWIFERY CARE FOR WOMEN WITH OLIGOMENORRHEA - Gita Yanti Simamora, Gita; Kamelia Sinaga; Rumondang Sitorus; Maria Gabriela Simanjuntak; Insawani Manalu (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Oligomenorrhea is a menstrual disorder characterized by menstrual cycles lasting more than 35 days and commonly occurs in adolescents due to hormonal imbalance. This condition may be influenced by several factors, including stress, irregular sleep patterns, excessive physical activity, poor nutritional status, and unhealthy lifestyle habits. Menstrual disorders in adolescents require special attention because they can negatively affect reproductive health, psychological well-being, daily activities, and future quality of life. Based on an assessment conducted on Ms. A, a 14-year-old adolescent living in Dusun I, Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency, irregular menstruation with prolonged cycles was identified, requiring comprehensive community midwifery care. Objective: This case study aimed to provide community midwifery care to an adolescent experiencing oligomenorrhea and to improve her knowledge, attitudes, and behaviors related to reproductive health.Method: A case study design was applied using a midwifery care management approach consisting of assessment, diagnosis and problem identification, planning, implementation, and evaluation. The interventions included counseling regarding oligomenorrhea, health education on balanced nutrition, recommendations for adequate rest, stress management strategies, regular light physical exercise, and psychological support for both the client and her family. Results: The interventions demonstrated positive outcomes. The client experienced reduced anxiety, improved sleep quality, more regular physical activity, and healthier dietary habits. At the final evaluation, the client reported that her menstrual cycle had returned to normal, menstruation lasted six days, and her overall physical and psychological condition had improved. Conclusion: Community midwifery care was effective in managing oligomenorrhea through health education, lifestyle modification, stress management, and family support, resulting in improved reproductive health knowledge and healthier behaviors among adolescents.